Roll with the Times, or the Times Roll Over You Charleston Conference Proceedings, 2016 - Strauch, Katina; Hinds, Leah; Bernhardt, Beth R. (Purdue University Press, 2017)
Over one hundred presentations from the 36th annual Charleston Library Conference (held November 1-5, 2016) are included in this annual proceedings volume. Major themes of the meeting included data visualization, streaming video, analysis and assessment, demand-driven acquisition, and open access publishing. While the Charleston meeting remains a core one for acquisitions librarians in dialog with publishers and vendors, the breadth of coverage of this volume reflects the fact that this conference is now one of the major venues for leaders in the publishing and library communities to shape strategy and prepare for the future. Almost 2,000 delegates attended the 2016 meeting, ranging from the staff of small public library systems to the CEOs of major corporations. This fully indexed, copyedited volume provides a rich source for the latest evidence-based research and lessons from practice in a range of information science fields. Contributors comprise leaders in the library, publishing, and vendor communities.